Modulasi Kadar Pati Resisten Berbagai Pangan Karbohidrat melalui Pemanasan Microwave: Meta-Analisis - Sugoi Marsaputra Karsodimejo; Feri Kusnandar; Hanifah Nuryani Lioe; Anuraga Jayanegara (Perhimpunan Ahli Teknologi Pangan Indonesia bekerjasama dengan Departemen Ilmu dan Teknologi Pangan, IPB University Bogor, Indonesia, 2023)
Starch is extensively utilized in food processing for various purposes. However, the use of native starch is limited due to its unsuitability with processing conditions or products characteristics. Physical modification of starch is commonly employed to enhance the properties of native starch. The physical starch modification using microwave heating is presently developed due to its more efficient energy consumption than that of traditional heating methods. The process of microwave heating followed by cooling has been found to induce the formation of type 3 resistant starch (RS3). However, the effects of microwaving heating towards the the increase of resistant starch contents varies among researchers. For this reason, a meta-analysis was conducted to evaluate the effect of microwave heating on the levels of resistant starch in carbohydrate sources such as cereals, pulses, and tubers. The objective of this study was to analyze the carbohydrate food groups that demonstrated the most significant increase in resistant starch levels due to microwave heating, and to determine the optimal microwave treatment parameters within these food groups using meta-analysis. The findings indicate that microwave heating treatment is particularly effective for cereals, with rice being the most responsive. The most favorable treatment parameters include a power range of 401-600 W, heating time of 60-99 s, and starch moisture content of 40-60%.